The South Asian Health Foundation (UK) guidelines for managing diabetes during Ramadan. (June 2020) - Hanif, W.; Patel, V.; Ali, S.N.; Karamat, A.; Saeed, M.; Hassanein, M.; Syed, A.; Chowdhury, T.A.; Farooqi, A.; Khunti, K.
Abstract: Background: Fasting in the holy month of Ramadan is among the five pillars of Islam and is considered as a religious obligation by the Muslim population. People with diabetes observing the practice of fasts are at a higher risk of complications such as hypoglycaemia, hyperglycaemia and ketoacidosis due to changes in eating patterns and circadian rhythms. With the objective of mitigating these complications, the South Asian Health Foundation (UK) has developed the present guidelines based on robust evidence derived from epidemiological studies and clinical trials. Methods: We have highlighted the role of pre-Ramadan risk stratification and counselling by healthcare professionals with emphasis on the need for advice on adequate dietary and fluid intake, blood glucose monitoring and awareness of when to break the fast. Results: We reviewed the current literature and have given clinically-relevant recommendations on lifestyle modifications and glucose-lowering therapies such as metformin, sulphonylureas, dipeptidyl peptidase-4 inhibitors, sodium glucose co-transporter-2 inhibitors, thiazolidinediones, glucagon-like peptide-1 receptor agonists and insulin. Conclusions: An individualised patient-centric treatment plan is essential to not only achieve optimal glycaemic outcomes but also enable people with diabetes to observe a risk-free month of fasting during Ramadan.